From Individual Heroes to National Performers: The Shift in Taekwondo’s Peace Promotion Activities - John A. Johnson (Physical Activity Review, 2020)
The writings of early taekwondo pioneers promote peace through the practice of the martial art and, later, the combat sport. These pioneers charged taekwondo practitioners with a duty to contribute to justice, defend the weak, and build a more peaceful world. National and international taekwondo organizations such as the Kukkiwon, World Taekwondo (WT), and the International Taekwon-Do Federation (ITF) have taken up the charge of peace promotion through taekwondo by means of tr ansnational events, such as goodwill tours and joint taekwondo demonstrations by adversarial states (e.g., South and North Korea). These activities are soft diplomacy initiatives and have seen some level of success. While these soft diplomacy activities are in line with the goal of peace promotion that the early pioneers advocated, they are qualitatively different from what the pioneers advocated. Originally, the responsibility of peace promotion was on the individual taekwondo practitioner, who ought to cultivate moral character, courage, and martial art skill in order to uphold justice and defend the weak. With the current use of taekwondo for soft diplomacy, the responsibility of peace promotion has shifted from the individual practitioner to the governing bodies, such as WT and the ITF. Instead of focusing on issues surrounding justice and the protection of the weak, these national and international organizations focus on geopolitical cooperation, which is mediated through cultural exchange activities in the form of taekwondo demonstrations. These events involve activities such as acrobatic performances, dance routines, and board breaking that require little combat skill and may not pose the risk of serious injury to the individual practitioners, mainstays of the individual heroes of old. The charge to safeguard justice and physically defend the weak, which are acts of true courage as was envisioned by the taekwondo pioneers, is mostly ignored.